2017
DOI: 10.1007/s00405-017-4808-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of systemic and intratympanic corticosteroid combination therapy versus intratympanic or systemic therapy in patients with idiopathic sudden sensorineural hearing loss: a randomized controlled trial

Abstract: 1b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…The analysis revealed that combined therapy seems to confer a certain degree of benefit as primary treatment of SSNHL compared with only systemic treatment. In a randomised, triple-blind, controlled trial in 2017 23 on 112 patients, 32 received IT corticosteroids, 45 received systemic corticosteroids and 35 received a combination of the two. No differences were found in hearing recovery between the three therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis revealed that combined therapy seems to confer a certain degree of benefit as primary treatment of SSNHL compared with only systemic treatment. In a randomised, triple-blind, controlled trial in 2017 23 on 112 patients, 32 received IT corticosteroids, 45 received systemic corticosteroids and 35 received a combination of the two. No differences were found in hearing recovery between the three therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The titles and abstracts of the remaining 435 articles were checked, and 202 full-text articles were further appraised. We finally identified 20 RCTs, 2,10,[13][14][15][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] including 1716 patients eligible for the analysis on the prognosis of SSHL ( Figure 1). All included RCTs were evaluated to be at low risk of bias via Cochrane risk of bias tool (see online appendix).…”
Section: Included Studies and Baseline Characteristics Of Participantsmentioning
confidence: 99%
“…Kedvezőtlen prognosztikai faktornak találtuk a magas frekvenciákon kialakult halláscsökkenést [22]. Betegeinknél a legkisebb javulást 8000 Hz-en, míg a legjelentősebbet 125 Hz-en tudtuk regisztrálni.…”
Section: áBraunclassified